Pengaruh Literasi Keuangan, Overconfidence, dan Faktor Demografi Terhadap Keputusan Investasi (Studi Kasus Pada Mahasiswa Akuntansi UPN â€œVeteranâ€ Jawa Timur) - Fitriani, Devy Julia; Sundari, Siti (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims..to..determine the effect of financial literacy, overconfidence, and demographic factors on the investment decisions of UPN "Veteran" East Java accounting students. Accounting students at UPN "Veteran" East Java class of 2019, totaling 293 students are the population used in this study. The Slovin formula was used to calculate the sample size for this investigation, which resulted in a final sample size of 75 students. The sampling technique used is simple random sampling and the data collection technique uses a questionnaire. The analytical method used is Structural Equation Modeling (SEM) analysis with the help of an analysis tool, namely SmartPLS 3.0..The results showed that financial literacy and overconfidence had a significant positive effect on investment decisions. Meanwhile gender and age are demographic criteria that show no effect on investment decisions.